It takes a village: Investigating the scaffolding strategies of writing development to support early literacy among Nova Scotians of African descent communities - Kalindi, Sylvia Chanda; Brigham, Susan; Frempong, George (Language and Literacy / Langue et littératie, 2024)
Several stakeholders, such as community groups, government officials, parents, guardians, and educators have shown concern about the achievement gap between Nova Scotia learners of African descent and their predominantly White peers. Using the African proverb ‘It takes a village’ as a framework, this study involved parents, extended family members and caregivers of children aged 4 to 6 years to explore the scaffolding strategies employed as well as the experiences of participants when supporting children’s emergent writing skills during COVID-19 pandemic. Survey and focus group sessions demonstrated how participants frequently scaffolded emergent writing using highly effective strategies including Africentric approaches. The importance of ‘It takes a village’ proverb in enhancing literacy developmenthas also been established.